2011
DOI: 10.2176/nmc.51.148
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Germinoma Presenting With Hemiatrophy- Follow-up Results and Literature Review -Two Case Reports-

Abstract: Two boys aged 8 and 12 years presented with intracranial germinoma manifesting as cerebral hemispheric atrophy, hemiparesis, and decline in academic performance. First magnetic resonance (MR) imaging showed no enhanced lesions, but follow-up MR imaging obtained 12 or 23 months after the first visit showed new mass lesions in the temporal lobe or pituitary gland. Biopsy of these lesions resulted in a histological diagnosis of germinoma. Chemoradiation therapy produced complete remission but both patients contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…[10,23,30] Our imaging findings most likely provide evidence for this clinical problem. Aggravated ipsilateral atrophy of the brain and cerebral peduncle can be observed in the patient who underwent longitudinal MR studies over 2 years.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…[10,23,30] Our imaging findings most likely provide evidence for this clinical problem. Aggravated ipsilateral atrophy of the brain and cerebral peduncle can be observed in the patient who underwent longitudinal MR studies over 2 years.…”
Section: Discussionmentioning
confidence: 82%
“…[7–9] Some reports have suggested that the hemiatrophy was the imaging feature of germinomas arising from the basal ganglia and thalamus. [2,10,11] The explanation for this sign was attributed to the infiltration of white matter tracts by the tumors. [8] However, to our knowledge, there is no report using diffusion tensor imaging (DTI) to visualize the involved white matter fiber tracts.…”
Section: Introductionmentioning
confidence: 99%
“…Intracranial germinomas that are off-midline (mainly basal ganglia) may present as progressive hemispheric dysfunction 6. Most present with haemiparesis and about half of patients develop cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Pineal tumours occur twice as often as suprasellar germ cell tumours, with a 2:1–3:1 male preponderance. Intracranial germinomas arise in off-midline regions, such as the basal ganglia, thalamus and cerebral hemispheres, in 4%–20% of cases 6. Pineal lesions usually present with early signs and symptoms of raised intracranial pressure from obstructive hydrocephalus, such as headache, papilloedema and altered mental status.…”
Section: Discussionmentioning
confidence: 99%
“…Kalsifikasyon nadirdir. Özellikle erken dönemde belirgin kontrastlanma görül-meyebilir [8]. MRS'de laktat-lipid piki, NAA/ kreatin oranında azalma görülür.…”
Section: Bazal Ganglion Germinomuunclassified